Cancer-associated fibroblasts as targets for immunotherapy - Kakarla, Sunitha (2012)
Immunotherapy for solid tumors has shown promise in preclinical as well as early clinical studies. However, its efficacy remains limited. The hindrance to achieving objective, long-lasting therapeutic responses in solid tumors is, in part, mediated by the dynamic nature of the tumor and its complex microenvironment. Tumor-directed therapies fail to eliminate components of the microenvironment, which can reinstate a tumorigenic milieu and contribute to recurrence. Cancer-associated fibroblasts (CAFs) form the most preponderant cell type in the solid tumor microenvironment. Given their pervasive role in facilitating tumor growth and metastatic dissemination, CAFs have emerged as attractive therapeutic targets in the tumor microenvironment. In this article, we highlight the cross-talk between CAFs and cancer cells, and discuss how targeting CAFs has the potential to improve current immunotherapy approaches for cancer.